SINTESIS, KARAKTERISASI, DAN APLIKASI POLIANILIN SEBAGAI POLIMER KONDUKTIF DALAM TEKNOLOGI MODERN: A REVIEW - Rifa'i, Fitra Ahmad; Saputra, Dewa Kahfi; Apriliana, Mahatma; Abidin, Luthfa Abibah Nur; Harjono, Harjono (Indonesian Journal of Pure and Applied Chemistry, 2025)
Polyaniline (PANI) is a widely studied conductive polymer known for its high electrical conductivity, environmental stability, and ease of synthesis. This review critically summarizes the chemical and electrochemical synthesis routes of PANI, along with its structural and electronic characterization using FTIR, UV"“Vis Spectroscopy, X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), electrical conductivity analysis, and X-ray Photoelectron Spectroscopy (XPS). Furthermore, it highlights the recent advancements in PANI applications across modern technologies, including chemical sensors, biosensors, supercapacitors, lithium-ion batteries, and biomedical devices. By analyzing 68 peer-reviewed articles published within the last decade, this work emphasizes the impact of synthesis parameters and structural modifications on the functional performance of PANI. While PANI offers promising potential, challenges like poor solubility and mechanical limitations remain. This review aims to bridge synthesis, structure, and application relationships and propose future directions for enhancing PANI"™s multifunctionality through nanocomposites and dopant engineering.